Analysis of the Competency-Based Clinical Nurse Career Path Development System Implementation - Elisabeth Longge; Rina Anindita; Rian Adi Pamungkas (Indonesian Journal of Global Health Research, 2021)
Nurses are one of important human resources in a hospital and are one of the keys to the successful implementation of services in the hospital. Providing opportunities in the form of career development is very important for the hospital to organize. The purpose of this study was to analyze the gap between the level of importance and implementation of career development at the UKI hospital in terms of the management and nurse executives perceptions. This research is a quantitative and qualitative research. The results of the study found that the negative average gap (-0.09) between the level of importance and implementation in terms of management and nurse perceptions was low. Based on the results of the study, it was concluded that the gap between the level of importance and implementation at the UKI Hospital judging from the management and nurses perception was still in the fair category. The research result can be used as material for reference and the study in the field of nursing science, particularly in the field of nursing management related to perceptions of career development with the quality of hospital services.